Modeling the volatility of Asian REIT markets. (1st September 2016) - Loo, Wei Kang; Ahmad Anuar, Melati; Ramakrishnan, Suresh
Abstract: This paper analyzed the volatility behavior of Asian real estate investment trust (REIT) markets. The autoregressive conditional heteroscedasticity (ARCH)-family models were applied for the purpose of conducting the in-sample fitting test and out-of-sample forecasting test. Results showed that the fractional integrated EGARCH model was the best model in forecasting the volatility for most of the Asian REIT markets. The outcome of this study would be useful for REIT investors in understanding the volatility of the Asian REIT markets. Similarly, policy-makers can also make use of this information to create derivate pricing for the future.